2002
DOI: 10.1073/pnas.142287999
|View full text |Cite
|
Sign up to set email alerts
|

HIV envelope induces a cascade of cell signals in non-proliferating target cells that favor virus replication

Abstract: Certain HIV-encoded proteins modify host-cell gene expression in a manner that facilitates viral replication. These activities may contribute to low-level viral replication in nonproliferating cells. Through the use of oligonucleotide microarrays and high-throughput Western blotting we demonstrate that one of these proteins, gp120, induces the expression of cytokines, chemokines, kinases, and transcription factors associated with antigen-specific T cell activation in the absence of cellular proliferation. Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
148
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 48 publications
13
148
0
Order By: Relevance
“…Our data suggest that the presence of Nef in HIV-infected cells, although rendering these cells unable to express antigen-specific effector functions, ensure a level of cellular activation that favor HIV replication and the suppression of the immune surveillance. This evidence is in agreement with recent findings obtained by using gene expression profiling revealingthat the two HIV-encoded proteins Nef and gp120 promote kinases and transcription factors associated with antigen-specific T cell activation and viral replication [50,51]. Moreover, our evidence that Vav can circumvent the immunological defects by reconstituting all features of full T cell activation, suggests that a strategy to overcome the problem of viral reservoirs could associate highly active antiretroviral therapy (HAART) to cytoskeleton activators.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that the presence of Nef in HIV-infected cells, although rendering these cells unable to express antigen-specific effector functions, ensure a level of cellular activation that favor HIV replication and the suppression of the immune surveillance. This evidence is in agreement with recent findings obtained by using gene expression profiling revealingthat the two HIV-encoded proteins Nef and gp120 promote kinases and transcription factors associated with antigen-specific T cell activation and viral replication [50,51]. Moreover, our evidence that Vav can circumvent the immunological defects by reconstituting all features of full T cell activation, suggests that a strategy to overcome the problem of viral reservoirs could associate highly active antiretroviral therapy (HAART) to cytoskeleton activators.…”
Section: Discussionsupporting
confidence: 92%
“…T cells upon contact with noninfected MDC undergo activation, which leads to the upregulation of HLA-DR, CD25, and CD69 (31). According to earlier data, activation of T cells is one of prerequisites for productive HIV replication (8,22,28). We found that even a low amount of HIV released by the long-term infected MDC was sufficient to rapidly spread infection in the MDC-T-cell microenvironment.…”
Section: Downloaded Fromsupporting
confidence: 60%
“…ϩ T cells to apoptose in vitro (12)(13)(14)(15). Envelope proteins have also been shown to disrupt antigen-specific CD4 ϩ T cell responses (16).…”
Section: Iv-1 Infection Of Cd4mentioning
confidence: 99%
“…In vitro exposure of resting CD4 ϩ T cells derived from HIV-infected individuals to envelope results in a burst of viral replication (19). Insight into the mechanisms that produce this burst was obtained from a study of the gene expression profiles in peripheral blood mononuclear cells (PBMCs) treated with gp120 derived from an R5 strain of HIV (14). Envelope treatment induced the expression of multiple factors that promote viral replication.…”
Section: Iv-1 Infection Of Cd4mentioning
confidence: 99%